2000
DOI: 10.1084/jem.191.10.1649
|View full text |Cite
|
Sign up to set email alerts
|

Human Cd4+ T Lymphocytes Consistently Respond to the Latent Epstein-Barr Virus Nuclear Antigen Ebna1

Abstract: The Epstein-Barr virus (EBV)-encoded nuclear antigen EBNA1 is critical for the persistence of the viral episome in replicating EBV-transformed human B cells. Therefore, all EBV-induced tumors express this foreign antigen. However, EBNA1 is invisible to CD8+ cytotoxic T lymphocytes because its Gly/Ala repeat domain prevents proteasome-dependent processing for presentation on major histocompatibility complex (MHC) class I. We now describe that CD4+ T cells from healthy adults are primed to EBNA1. In fact, among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
266
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(288 citation statements)
references
References 67 publications
(79 reference statements)
11
266
3
Order By: Relevance
“…EBNA-1-specific CD4ϩ T cells (45,46), mainly of the Th1 phenotype (47), have recently been detected in healthy EBV carriers and may provide help for the production of antibodies directed to the different epitopes of this protein. In the presence of a higher EBV load, events such as apoptosis, infection, damage, or any stimulus involving calcium influx may activate PAD, which is highly expressed in RA synovia (48,49), and induce the deimination of different proteins, including viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…EBNA-1-specific CD4ϩ T cells (45,46), mainly of the Th1 phenotype (47), have recently been detected in healthy EBV carriers and may provide help for the production of antibodies directed to the different epitopes of this protein. In the presence of a higher EBV load, events such as apoptosis, infection, damage, or any stimulus involving calcium influx may activate PAD, which is highly expressed in RA synovia (48,49), and induce the deimination of different proteins, including viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…EBV nuclear antigen 1 (EBNA-1) is a latent antigen that is invariably expressed in all EBV-infected proliferating cells [16] and associated malignancies [17], being crucial for viral persistence by acting as replication and transcription factor [18], without viral particle formation. EBNA-1 is an immunodominant latent target of EBVspecific CD4 1 T cells [19,20]. Although it has been described in the past to escape from recognition by CD8 1 T cells due to Gly/Ala repeated domains preventing proteasome-dependent processing for presentation on MHC class I [21], more recent studies revealed the existence of EBNA-1-specific CD8 1 T cells [15,22,23].…”
mentioning
confidence: 99%
“…Subsequently, presentation of endogenous proteins on MHC class II has been described for a number of other viral antigens [28][29][30][31] as well as self-antigens, 21,32-34 model antigens, [35][36][37][38][39][40] and tumor antigens 41,42 (Table 2). On the basis of these findings, four endogenous MHC class II processing pathways can be postulated [43][44][45] (Figure 1).…”
Section: Endogenous Mhc Class II Processingmentioning
confidence: 99%
“…47 In addition to these proteasome-dependent pathways, cytosolic and nuclear proteins can also be processed by a proteasome-and TAPindependent pathway: This fourth pathway involves the direct import of cytosolic/nuclear proteins (e.g. the EBV nuclear antigen 1 (EBNA1) 30,31 ) into endosomes/lysosomes and is in part mediated by autophagy. The latter three pathways (processing of cytosolic or nuclear proteins by proteasomedependent or -independent mechanisms) contribute more than 20% of endogenous MHC class II ligands.…”
Section: Endogenous Mhc Class II Processingmentioning
confidence: 99%